A Histological Study of Pathological Changes in the Rat Thyroid Gland Induced by Chronic Ultraviolet-A (UVA) Radiation Exposure According to Exposure Duration (Al-Farooq Journal of Sciences, 2026)
The thyroid gland is one of the most important endocrine glands responsible for regulating metabolism, growth, and physiological homeostasis in the body. With the increasing exposure to ultraviolet-A (UVA) radiation, growing attention has been directed toward investigating its potential effects on biological tissues.Aim of the Study:This study aimed to evaluate the histological effects induced by ultraviolet-A (UVA) radiation exposure on the follicular structure of the thyroid gland in adult albino rats and to investigate the relationship between these effects and the duration of exposure.Materials and Methods: Twenty adult male albino rats were equally divided into four groups: Group I: Control group. Group II: Exposed to ultraviolet radiation for 10 consecutive days at a rate of 8 hours daily. Group III: Exposed to ultraviolet radiation for 15 consecutive days at a rate of 8 hours daily. Group IV: Exposed to ultraviolet radiation for 25 consecutive days at a rate of 8 hours daily. At the end of the experiment, the thyroid glands were excised, and tissue specimens were prepared for histological examination using hematoxylin and eosin staining.Results: The histological examination of the thyroid glands revealed progressive structural alterations in the exposed groups compared to the control group. These changes included disruption of follicular architecture, variation in follicular size, vascular congestion, reduction of colloid content, epithelial cell crowding, and morphological alterations in epithelial cell shape. The severity of these changes increased progressively with longer exposure duration, being most pronounced in the 25-day exposure group.Conclusion: The findings indicate that chronic exposure to ultraviolet-A (UVA) radiation induces cumulative harmful histological effects on the thyroid gland, with severity increasing in proportion to exposure duration, which may adversely affect its functional efficiency.
Keywords: Ultraviolet-A radiation, Thyroid histopathology, Oxidative stress, Endocrine disruption, Albino rat model, Photo biological toxicity